Entwurf eines fehlertoleranten Lenkventils für Steer-by-Wire Anwendungen bei Traktoren - Schmitz, David (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2014)
In this thesis a hydrostatic steer-by-wire valve with independent metering edges is analysed regarding its usability in safety critical applications. Doing experimental investigations it is shown, that valve faults can be compensated by the system in order to guarantee the steerability. Because of the chosen valve concept and the fact that valve faults can be detected without position sensors at each valve, the system complexity of the chosen solution is low.